Knowledge, attitudes and practices on tsetse and sleeping sickness among communities living in and around Serengeti National Park, Tanzania - Kinung'hi, SM; Malele, II; Kibona, SN; Matemba, LE; Sahani, JK; Kishamawe, C; Mlengeya, TDK (Tanzania Journal of Health Research, 2009)
No Abstract.